Skim agihan zakat asnaf al-ghārimīn di institusi-institusi zakat di Malaysia - Ismail, Halim; Daud, Mohd Noor (Penerbit USIM, 2017)
This study investigated the implementation of the scheme of distribution of zakah al- Ghārimin recipients by selective zakat institutions in Malaysia. This study was conducted using qualitative research methods and analyzed using the method of deductive, inductive and comparison. Studies show that the schemes zakah al-Ghārimin recipients implemented varies between institutions of zakah in Malaysia. There are schemes implemented by all the institutions of zakah surveyed, while there are also schemes implemented by certain zakah institutions. This study has implications for the implementation of the scheme of distribution of zakah recipients al- Ghārimin by institutions of zakah in Malaysia.